Newman's Error Analysis: The Errors of 4th Grade Students in Solving TIMSS Problems - Aziza, Mela; Eratika, Enisri (Jurnal Pendidikan Matematika, 2022)
Indonesian students who have low ability in mathematics require a lot of testing of international standard questions to practice their problem-solving and reasoning skills. Error analysis is needed to analyze the causes of student errors and how determine preventive solutions in the future. This study aims to determine the errors of fourth-grade students at SD Negeri 36 Lubuk Sirih Ilir Village in solving TIMSS (Trends in International Mathematics and Science Study) problems. A qualitative approach was used to collect qualitative descriptive data on students’ errors. The ability of each student is categorized based on the TIMSS benchmark, and the errors made are analyzed by Newman’s Error Analysis (NEA). The analysis activity steps for this study are collecting data, reducing, presenting, and drawing conclusions. Ten TIMSS problems that have been selected based on the content domains were tested on students, and the results showed that the abilities of eight students were in a low category, while one person with medium ability and one with very high ability. When students answered the TIMSS problems, they made the most errors in the numbers, measurement, and geometry domains.  All students gave incorrect answers to number 6, one of the measurement and geometry problems, meanwhile, in number 3, a problem of numbers domain, one participant answered correctly. According to the NEA, errors in understanding problems and process skills were the most common errors. The types of mistakes made by students can be an evaluation for teachers in determining strategies when asking questions in mathematics class. Kemampuan siswa Indonesia di bidang matematika yang rendah membutuhkan banyak pengujian soal standar internasional untuk melatih kemampuan pemecahan masalah dan penalaran mereka. Analisis kesalahan dibutuhkan untuk menganalisis penyebab kesalahan siswa dan bagaimana menentukan solusi pencegahan ke depannya. Penelitian ini bertujuan untuk mengetahui jenis-jenis kesalahan peserta didik kelas IV SD Negeri 36 Desa Lubuk Sirih Ilir dalam memecahkan soal TIMSS (Trends in International Mathematics and Science Study). Pendekatan kualitatif digunakan untuk mengumpulkan data kualitatif deskriptif tentang kesalahan peserta didik. Kemampuan setiap peserta didik dikategorikan berdasarkan tolak ukur TIMSS dan kesalahan yang dilakukan dianalisis dengan Newman’s Error Analysis (NEA). Langkah-langkah analisis yang dilakukan adalah pengumpulan data, reduksi, penyajian, dan pengambilan kesimpulan. Sepuluh soal TIMSS yang sudah diseleksi berdasarkan domain materi diujikan kepada peserta didik dan hasilnya menunjukan bahwa kemampuan delapan peserta didik berada pada kategori rendah sedangkan satu orang berkemampuan sedang dan satu lainnya memiliki kemampuan sangat tinggi. Ketika menjawab soal TIMSS, peserta didik melakukan kesalahan paling banyak pada domain materi bilangan serta pengukuran dan geometri. Pada salah satu soal pengukuran dan geometri yaitu nomor 6, semua peserta didik memberikan jawaban yang salah. Sedangkan pada soal materi Bilangan nomor 3, hanya satu peserta yang tidak melakukan kesalahan dalam menjawab. Berdasarkan NEA, kesalahan dalam memahami soal dan keterampilan proses adalah kesalahan yang paling banyak dilakukan. Jenis kesalahan yang dilakukan siswa bisa menjadi evaluasi bagi guru dalam menentukan strategi dalam aktivitas bertanya di kelas matematika.